2016
DOI: 10.1002/eat.22643
|View full text |Cite
|
Sign up to set email alerts
|

The risk of eating disorders comorbid with attention‐deficit/hyperactivity disorder: A systematic review and meta‐analysis

Abstract: Ha habido interés en saber si la gente con Trastorno por Déficit de Atención e Hiperactividad (TDAH) están en mayor riesgo de desarrollar un Trastorno de la Conducta Alimentaria (TCA). El objetivo de este estudio fue estimar el tamaño de esta asociación con un meta-análisis de los estudios. Métodos: Recuperamos estudios de una amplia gama base de datos,  que siguen los lineamientos PRISMA. Resultados: Doce estudios encajaron con nuestro objetivo primario de investigar los TCA en poblaciones con TDAH (TDAH = 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 85 publications
(192 reference statements)
8
112
0
6
Order By: Relevance
“…There is a growing literature that humans are at risk for comorbid conditions, so that estimated PODs may be similar (e.g., within an order of magnitude) across a set of analyses. For example, neurodevelopment may impact impulsive behavior, which may lead to over-eating and to obesity (Nazar et al, 2016). The analysis of impulsive behavior may provide useful HBM values also to measures of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing literature that humans are at risk for comorbid conditions, so that estimated PODs may be similar (e.g., within an order of magnitude) across a set of analyses. For example, neurodevelopment may impact impulsive behavior, which may lead to over-eating and to obesity (Nazar et al, 2016). The analysis of impulsive behavior may provide useful HBM values also to measures of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize shortly, the complex relationships between ADHD and eating disorder not just rely on single factors (e.g., impulsivity, genetic abnormalities, depression), but the interactions among these factors might interpret the associations. It has been suggested that not only ADHD neuropsychological functioning could alter information processing for food-related decision making, but also changes in nutritional or emotional state promoted by eating disorder could make ADHD individuals more prone to disinhibition 16 .…”
Section: Discussionmentioning
confidence: 99%
“…An updated meta-analysis study indicated that people with ADHD are 3.8 times more likely to present with any eating disorder as a comorbid diagnosis, and the risk increased to 5.7 times for Bulimia Nervosa 16 . Bulimia Nervosa is characterized by recurrent episodes of binge eating, and recurrent inappropriate compensatory behavior in order to prevent weight gain 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental disorders have been associated with eating disorders (ED), with attention-deficit/hyperactivity disorder linked to bulimia nervosa (BN) and binge-eating disorder (Nazar et al, 2016), and autism spectrum disorders (ASDs) to anorexia nervosa (AN) ( Baron-Cohen et al, 2013;Tchanturia et al, 2013). There has been interest in the impact these might have upon treatment and prognosis (Westwood & Tchanturia, 2017).…”
Section: Introductionmentioning
confidence: 99%